Management of Obstructive Sleep Apnoea in a Patient with Pierre Robin Sequence by Using Distraction Osteogenesis - Mohamed Hisham Mohamed Jali; Shaifulizan Abdul Rahman; Ramizu Shaari (USIM Press, 2024)
MJoSHT 2021, Volume 7, Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience. eISSN: 2601-0003